Determinants of HPV vaccine uptake intentions in Chinese clinical interns: an extended theory of planned behavior approach - Wang, Huizi; Xu, Yuedong; Zhang, Hui; Chen, Ning (Frontiers in Public Health, 2024)
This study aims to utilize the extended Theory of Planned Behavior (TPB) model to examine the intentions of clinical interns in China towards Human papillomaviruses(HPV) vaccination. It also fills a significant gap in the literature concerning vaccine acceptance in this specific population.This cross-sectional study was carried out with clinical interns in Shandong Province, China, with a total of 1,619 participants. Data were collected through self-reported questionnaires, including demographic characteristics, TPB variables, and HPV-related health knowledge.Hierarchical regression analysis was employed to identify key factors influencing vaccination intentions, and Structural Equation Modeling (SEM) was used to analyze the interrelationships between these factors.This study initially identified key predictors affecting clinical interns' intentions to receive the HPV vaccine through hierarchical regression analysis. The preliminary model, which accounted for demographic factors, revealed foundational impacts of household income and HPV-related clinical experience on intentions. After integrating TPB variables-attitude, subjective norm, perceived behavioral control, and HPV-related health knowledge-the model's explanatory power was enhanced to 37.30%. SEM analysis focused on the interplay among TPB constructs and extended variables, confirming their significance in forming vaccination intentions, with subjective norm having the most substantial impact (β = 0.375, p < .001). The extended TPB model explained over half of the variance in vaccination intentions, substantiating the hypotheses and revealing the psychological determinants behind clinical interns' decision-making for HPV vaccination.The extended TPB model from this study effectively explains the vaccination intentions among clinical interns for HPV, offering theoretical support for public health strategies and